An examination of selected works for percussion: Black sphinx by Leander Kaiser, To the Gods of rhythm by Nebojsa Zivkovic, Regresar a Nuestra by Stephanie Sasscer, Wave, How Insensitive and Agua de Beber by Antonio Carlos Jobim, Concerto pour vibraphone et piano by Emmanuel Sejourne, 6 & 8 by Tobias Brostrom, Suomineito by Nebojsa Zivkovic, Conververgences by Steve Fitch - Dease, Emory Christian (Kansas State University, 2010)
This is a report intended to assist in educating musicians planning to perform or study any number of the following compositions: Black Sphinx by Leander Kaiser, To the Gods of Rhythm by Nebojsa Jovan Zivkovic, Regresar a Nuestra by Stephanie Sasscer, Wave, How Insensitive, Agua de Beber by A.C. Jobim, Concerto for Vibraphone, movement I by Emmanuel Sejourne, 6 & 8 by Tobias Brostrom, Suomineito by Nebojsa Jovan Zivkovic, and Convergences by Steve Fitch. Each composition has been analyzed in accordance with Jan LaRue’s method of style analysis. For some compositions, analysis of harmony has been omitted. For all compositions, the author has analyzed essential technical and interpretive performance considerations according to LaRue’s analytical method. LaRue’s method includes analysis of Sound, Harmony, Melody, Rhythm, Growth and Performance.
Keywords: Percussion; Vibraphone; Zivkovic; Sejourne; Fitch; Brostrom; Music (0413)